2019
DOI: 10.3835/plantgenome2018.05.0029
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide Association Mapping and Prediction of Adult Stage Septoria tritici Blotch Infection in European Winter Wheat via High‐Density Marker Arrays

Abstract: Core Ideas Elite European winter wheat varieties hold large genetic variance for resistance to Septoria tritici blotch (STB) infection. Genome‐wide association studies with high‐density marker platforms identified hitherto undetected genetic loci for STB infection. Genomic prediction suggested the effective use of genomic selection for STB resistance Septoria tritici blotch (STB) caused by the fungus Zymoseptoria tritici is a devastating foliar disease of wheat (Triticum aestivum L.) that can lead to substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 82 publications
12
62
0
Order By: Relevance
“…In our study, the size of the population, high-density genotyping, and the use of stringent linear mixed-effect models warranted the genetic mapping of true marker-trait-associations (MTA). As noted in another study based on a subset of varieties, the absence of distinct sub-populations in this panel suggests that the European winter wheat varieties have been bred, by and large, from a narrow genetic base and with similar goals (Muqaddasi et al 2019) which is in line with other reports based on studies using similar genetic material but different marker platforms (Kollers et al 2013; Würschum et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the size of the population, high-density genotyping, and the use of stringent linear mixed-effect models warranted the genetic mapping of true marker-trait-associations (MTA). As noted in another study based on a subset of varieties, the absence of distinct sub-populations in this panel suggests that the European winter wheat varieties have been bred, by and large, from a narrow genetic base and with similar goals (Muqaddasi et al 2019) which is in line with other reports based on studies using similar genetic material but different marker platforms (Kollers et al 2013; Würschum et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, several studies based on 90K SNP arrays can be found which have used GWAS for kernel yield [20,64,65], for resistance against different diseases in wheat [62,66,67], and for bi-parental QTL mapping [32,[68][69][70][71]. Comparatively, GWAS-based linkage disequilibrium (LD) is a much more powerful tool to detect genetic loci in larger gene pools, with much higher resolution than traditional QTL mapping [72].…”
Section: Comparison Of Present Gwas Results With Previous Studiesmentioning
confidence: 99%
“…In addition, we detected 15 QTL whose positions overlapped with previously published QTL conferring resistance to STB (detailed in Figure 3 and Table S5). Of these, four QTL (QStb.teagasc-2D.1, QStb.teagasc-4B.1, QStb.teagasc-6D.2, and QStb.teagasc-7B.1) were co-located with published adult plant STB resistance QTL identified under German field conditions [76], while nine QTL co-located with QTL from a single previously published study of field STB resistance in Switzerland [74]. Notably, QStb.teagasc-7B.1 co-located with STB resistance QTL identified in both [74,76].…”
Section: Qtl Analysis and Comparison With Previously Reported Stb Qtlmentioning
confidence: 98%
“…Of these, four QTL (QStb.teagasc-2D.1, QStb.teagasc-4B.1, QStb.teagasc-6D.2, and QStb.teagasc-7B.1) were co-located with published adult plant STB resistance QTL identified under German field conditions [76], while nine QTL co-located with QTL from a single previously published study of field STB resistance in Switzerland [74]. Notably, QStb.teagasc-7B.1 co-located with STB resistance QTL identified in both [74,76]. As these QTL appear to have been identified in more than one country, this suggests they may provide sources of durable resistance against different pathogen populations and prevailing conditions.…”
Section: Qtl Analysis and Comparison With Previously Reported Stb Qtlmentioning
confidence: 98%
See 1 more Smart Citation